Learning Disabilities Today: An Examination of Effective and Not-So-Effective Interventions - Austin, Vance L. (Journal of the American Academy of Special Education Professionals, 2015)
The classification of "Specific Learning Disabilities" has experienced revision in the last decade due, in no small part, to the changes provided in IDEIA 2004. The "discrepancy clause" has been replaced with "…response to scientific, research-based intervention," for example. As a result, two new frameworks have been developed to ensure that students at risk for a learning problem or behavioral problem receive effective, research-based interventions to pre-empt the unwarranted classification of those students; namely, "Response to Intervention" relative to academic instruction, and "Positive Behavior Intervention and Supports" regarding student behavior. The article examines both these systems critically and suggests practical applications in today’s schools. Similarly, the author provides some effective strategies to address the characteristic learning challenges students with learning disabilities face in the classroom. The article concludes with an analysis of "Differentiated Instruction" and provides the reader with a "practical" way to differentiate the curriculum at all academic levels.